Clinical presentation and prevalence of uterine fibroids: a 3-year study in 3-decade rural South Indian women - Munusamy, Mohanambal M.; Sheelaa, Wills G.; Lakshmi, Vijaya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine fibroids are benign tumors arising from smooth muscle cells of myometrium. This study was conducted in rural women belonging to poor socio-economic class and primary school dropouts to find out clinical presentation, prevalence of uterine fibroids, their knowledge about health services and to develop modalities to improve awareness and early reporting to prevent morbidity and improve quality of life. Methods: Women ranging from 26-55 years age attending Gynecology OPD of SSSMCRI for abdominopelvic mass, pain, menstrual abnormalities over a period of 3 years were registered for the study. Socio-demographic profile, detailed menstrual history, reason for attending hospital and previous treatment taken prior to the hospital visit were recorded. Women with pregnancy with fibroids and fibroids detected by ultra-sonogram less than 12 weeks were excluded from the study. Clinical, local and ultra-sonographic examination was done for the morphology of the fibroids. Comparison was done with histological picture for accuracy in clinical and sonographic diagnosis. Results: 362 women who presented with uterine fibroids, menorrhagia or with abdomino pelvic mass were registered for this study. Of 136 patients who had uterine fibroids 66% had menorrhagia with severe anemia, 23% needed blood transfusion, 17 were nulliparous women. Menorrhagia was the commonest menstrual pattern seen in 58.8% women. Asymptomatic fibroids with huge abdomino pelvic mass was seen in 46 women (33%). The size was 12-28 weeks. The mean age was 46 years. Abdominal hysterectomy was done in 88 women, and 3 in-situ hysterectomies (91 cases) (67%), polypectomy in 16 and myomectomy in 22 nulliparous women. Laparotomy for torsion sub-serous fibroids was done in 7. Conclusions: Further research is needed to find out biological factors causing fibroids including diet, stress, environmental and racial influences. Routine screening, early detection, increase awareness by early reporting to the hospital will reduces morbidity and improves quality of life socioeconomically.